THAI AND NON-THAI INSTRUCTORS’ PERSPECTIVES ON PEER FEEDBACK ACTIVITIES IN ENGLISH ORAL PRESENTATIONS: 1st December 2022; 31st January 2023; 2nd March 2023; 4th March 2023 - Wanchid, Raveewan; Charoensuk, Valaikorn (PEOPLE: International Journal of Social Sciences, 2023)
The purposes of this research were 1) to investigate Thai and non-Thai teachers’ perspectives on peer feedback activities in English oral presentations; 2) to compare the perspectives on peer feedback activities of Thai and non-Thai teachers, and 3) to explore possible reasons affecting the Thai and non-Thai teachers’ perspectives on peer feedback activities in their real classroom practices. The study was conducted with 5 Thai and 5 foreign instructors. Questionnaires, interviews, and classroom observations were used to collect the data. Descriptive statistics and content analysis were employed in the data analysis. The results revealed that 1) in general both Thai and non-Thai instructors moderately agreed that peer feedback was beneficial for students, 2) the perspectives of Thai and non-Thai teachers in most items were not significantly different, and 3) there were six possible reasons why Thai and non-Thai teachers have different perspectives on some issues towards the use of peer feedback activities.